The Office of public private partnership (OPPP). (Asian Development Bank, 2019)
The Office of Public Private Partnership (OPPP) was established to enhance the role of ADB in supporting and enabling governments of its developing members to secure greater private investment and generate economic growth in the region. OPPP provides transaction advisory services to developing member clients in order to develop bankable PPP projects. It also coordinates and supports PPP related activities in ADB.